2005
DOI: 10.1073/pnas.0502903102
|View full text |Cite|
|
Sign up to set email alerts
|

Docosahexaenoic acid: A positive modulator of Akt signaling in neuronal survival

Abstract: Phosphatidylinositol 3-kinase [PI (3)K]/Akt signaling is a critical pathway in cell survival. Here, we demonstrate a mechanism where membrane alteration by the n-3 fatty acid status affects Akt signaling, impacting neuronal survival. Docosahexaenoic acid (DHA), an n-3 polyunsaturated fatty acid highly enriched in neuronal membranes, promotes neuronal survival by facilitating membrane translocation/activation of Akt through its capacity to increase phosphatidylserine (PS), the major acidic phospholipid in cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
319
0
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(342 citation statements)
references
References 49 publications
14
319
0
6
Order By: Relevance
“…As n-3 PUFA and BDNF have been implicated in the pathogenesis of bipolar disorder, this may be how n-3 PUFAs exert their effects in the disorder. Along with studies demonstrating DHA to be neuroprotective by increasing Atk 86 and syntaxin 3 87 signaling while decreasing proinflammatory gene expression, 88,89 oxidative stress, markers of synaptic loss, and behavioral defects in a mouse model of Alzheimer's disease, 90 the finding that dietary n-3 PUFAs can influence frontal cortex p38 MAPK, CREB and BDNF has implications for the role of n-3 PUFAs in a number of brain diseases.…”
Section: R E T R a C T E Dmentioning
confidence: 97%
“…As n-3 PUFA and BDNF have been implicated in the pathogenesis of bipolar disorder, this may be how n-3 PUFAs exert their effects in the disorder. Along with studies demonstrating DHA to be neuroprotective by increasing Atk 86 and syntaxin 3 87 signaling while decreasing proinflammatory gene expression, 88,89 oxidative stress, markers of synaptic loss, and behavioral defects in a mouse model of Alzheimer's disease, 90 the finding that dietary n-3 PUFAs can influence frontal cortex p38 MAPK, CREB and BDNF has implications for the role of n-3 PUFAs in a number of brain diseases.…”
Section: R E T R a C T E Dmentioning
confidence: 97%
“…Because DHA is a major constituent in neural membranes and has been shown to alter neuronal signaling pathways, 33 changes in DHA levels could have pathophysiological consequences. Recently, Laville et al reported that hamsters raised on an omega-3 FA deficient diet had higher diurnal and nocturnal locomotor activities that were associated with decreased levels of pineal melatonin during the dark phase and with increased levels of dopamine and its metabolites in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of the diet with these PUFAs may help to delay changes associated with neurodegenerative diseases such as PD [4]. Docosahexaenoic acid (DHA) is the major PUFA in the phospholipids fraction of the brain and is required for normal neuronal function [5]. Maintaining concentrations of this PUFA is essential for enhanced cognitive, learning and memory functions.…”
Section: Introductionmentioning
confidence: 99%